2018
DOI: 10.1186/s12957-018-1423-5
|View full text |Cite
|
Sign up to set email alerts
|

A study on the value of narrow-band imaging (NBI) for the general investigation of a high-risk population of nasopharyngeal carcinoma (NPC)

Abstract: BackgroundThis study aims to explore the feasibility of narrow-band imaging (NBI) applied for the diagnostic screening of a high-risk population of nasopharyngeal carcinoma (NPC) and increase the accuracy rate of nasopharyngeal biopsy and the diagnosis rate of early-stage patients.MethodsThe positive high-risk population of NPC to EB virus antibody was followed up. At the same time, serological screening and pharyngorhinoscopy were carried out. The specific methods were as follows: (1) all subjects received na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…In conclusion, early diagnosis and treatment should be actively carried out to reduce the incidence of nasopharyngeal carcinoma, such as strengthening the science popularization education of nasopharyngeal carcinoma, popularizing EB virus antibody test [ 22 , 23 ], conducting clinical trials of nasopharyngeal carcinoma vaccine, and improving the living habits and the quality of the ecological environment [ 3 , 24 ], especially for rural, ethnic Zhuang, and males in the 40–49-year age group patients. The future research on nasopharyngeal carcinoma will focus on exploring the pathogenesis of nasopharyngeal carcinoma, improving the screening system [ 25 ], reducing the burden on patients, and formulating individualized treatment strategies, in order to further improve the survival rate and quality of life of patients with nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, early diagnosis and treatment should be actively carried out to reduce the incidence of nasopharyngeal carcinoma, such as strengthening the science popularization education of nasopharyngeal carcinoma, popularizing EB virus antibody test [ 22 , 23 ], conducting clinical trials of nasopharyngeal carcinoma vaccine, and improving the living habits and the quality of the ecological environment [ 3 , 24 ], especially for rural, ethnic Zhuang, and males in the 40–49-year age group patients. The future research on nasopharyngeal carcinoma will focus on exploring the pathogenesis of nasopharyngeal carcinoma, improving the screening system [ 25 ], reducing the burden on patients, and formulating individualized treatment strategies, in order to further improve the survival rate and quality of life of patients with nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The studies reviewed by the cited authors used different diagnostic criteria, including vascular or mucosal abnormalities. 15,17,21,23 Thus, the cited authors suggested that NBI might be useful for diagnosis of NPC and that further work was needed. 28 Additional relevant studies have since been published.…”
Section: Discussionmentioning
confidence: 99%
“…After discharge from the hospital post-CCRT, all patients were required to be hospitalized for follow-up review every 3 months during the first year, every 4-6 months during the second to third years, and every 12 months after the third year. The following examinations were performed at each follow-up visit: (1) contrast-enhanced magnetic resonance imaging of the nasopharynx, skull base, and cervical lymph nodes; (2) chest computed tomography; (3) high-definition endoscopic examination through both the white-light and narrow-band imaging modes, as described in our previous study (24); (4) ultrasound of the entire abdomen; and (5) if necessary, 18 F-FDG positron emission tomography integrated with computed tomography to confirm suspected local tumor recurrence or distant relapse that could not be diagnosed by biopsy.…”
Section: Follow-upmentioning
confidence: 99%